2020
DOI: 10.1116/6.0000284
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of Si-doped conductive AlInN films grown nearly lattice-matched to c-plane GaN on sapphire by metalorganic chemical vapor deposition

Abstract: In this study, Si-doped conductive AlInN films with a thickness of 300 nm were grown nearly lattice-matched to c-plane GaN-on-sapphire templates by metalorganic chemical vapor deposition. A high net donor concentration of approximately 1 × 1019 cm−3 was observed for a highly Si-doped AlInN film. To evaluate its vertical-direction electrical resistivity without being affected by polarization-induced carriers, the transfer length measurement (TLM) model was applied to two kinds of test element groups. By analyzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was reported that Al 1−x In x N alloy grown by the same MOCVD reactor contained high-concentration of oxygen approximately on the order of 10 19 cm −3 and oxygen concentration gradually increased toward the surface from the interface. 33) Thus, it is expected that, in addition to the surface roughness and oxidation layers, the effect of high-concentration of oxygen including Al 1−x In x N possibly included in the surface-layer of the multi-layer model. Thicknesses of the surface-layer were estimated to be in a range of 5.6-9.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that Al 1−x In x N alloy grown by the same MOCVD reactor contained high-concentration of oxygen approximately on the order of 10 19 cm −3 and oxygen concentration gradually increased toward the surface from the interface. 33) Thus, it is expected that, in addition to the surface roughness and oxidation layers, the effect of high-concentration of oxygen including Al 1−x In x N possibly included in the surface-layer of the multi-layer model. Thicknesses of the surface-layer were estimated to be in a range of 5.6-9.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20] Furthermore, the carrier concentration of AlInN can be increased up to ∼10 19 cm −3 by Si and Ge doping. 21,22) The specific contact resistance at the AlInN/GaN interface is as low as 1.5 × 10 −7 Ω cm 2 , 21) and the vertical direction resistivity of a 300 nm thick AlInN layer is as low as 5.8 × 10 −4 Ωcm 2 . 22) These attributes make AlInN a desirable candidate as a sideetching layer material to initiate the formation of reverse tapered edge of GaN for power devices applications.…”
mentioning
confidence: 99%
“…
Ternary AlInN alloys are viewed as useful component materials for GaN-based electronic and optical devices, such as barrier layers in heterostructure field-effect transistors (HFETs), [1,2] or cladding layers, [3,4] distributed Bragg reflectors (DBRs), [5,6] and active layers [7,8] in light-emitting devices. For the past several years, we have conducted intensive research on the epitaxial growth and characterization of c-plane AlInN layers with thicknesses of around 300 nm using metal-organic chemical vapor deposition (MOCVD), [9][10][11][12][13][14][15][16][17][18] as primarily aiming at their application to cladding layers in GaN-based visible laser diodes (LDs). Through those studies, we found the following thing.
…”
mentioning
confidence: 99%